Nationalism as a factor in anti-Chalcedonian feeling in Egypt - Frend, W. H. C. (Studies in church history, 1982)
The writer of the History of the Patriarchs preserves an interesting tradition concerning the attitude of the monks of the monastery of Metras towards the Monophysite patriarch Benjamin (619-661/5)’ during the reign of the emperor Heraclius. ‘The inmates,’ we are told, ‘were especially powerful.’ They were Egyptians (Miswrani) by race, all natives, and there was no stranger among them. Therefore, Heraclius could not make their hearts pliant, and therefore they received Apa Benjamin when he returned from Upper Egypt, because they kept the orthodox (that is, Monophysite) faith and did not deviate from it’. Other monasteries might bow to ‘Heraclius the heretic’, but not they.